(untitled) (Interdisciplinary Studies Journal, 2024)
This study analyzes the narrative identity of an elderly guerrilla woman put into speech acts. The objective is to think about the aging processes and the identities of old guerrilla women in contemporary times. Through oral history we understand the need for listening in which the speech acts revealed in the voice of our narrator make the imaginaries and representations on which the understanding and identity of the old woman are based combine a claiming discourse that transforms the process of contemporary aging in a polyphonic experience. The analysis seeks to establish in a relational way the living conditions of her and other guerrillas in contemporary times. Based on their living conditions, their stories and the stories of others, through assumed behaviors and aspirations, they synthesize heterogeneous elements of the condition of being a woman and expose the identity contradictions that formulate diverse social trajectories, limited to complex networks of social relations , in which the durability of life reinvents female bodies and reinscribes contradictory characters and identities, but which complement each other in continuous recompositions of different identities, different temporalities in a body that is reunited with its experiences.